Meningkatkan Kemampuan Guru dalam Memanfaatkan Lingkungan Sekolah sebagai Sumber Belajar dengan Pelaksanaan Diskusi Terbimbing di MIN 12 Bandar Lampung Tahun Pelajaran 2022/2023 - Munashiroh, Munashiroh (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2023)
The purpose of this study was to determine the increase in the ability of teachers to use the school environment as a learning resource after carrying out guided discussion activities. This type of research is School Action Research consisting of two cycles with four stages of action namely planning, action implementation, observation and reflection. The research subjects were 10 (ten) teachers at Madrasah Ibtidaiyah (MIN) 12 Bandar Lampung. Data collection techniques are observation and field notes, the data of which is analyzed using qualitative and quantitative approaches. The results of the study were that in the pre-cycle the average teacher's ability to utilize the school environment as a learning resource was only 37.5%, increased in cycle I by 65% and in cycle II by 92.5%. The conclusion is that the implementation of guided discussion activities can improve the ability of teachers to utilize the school environment as a learning resource at MIN 12 Bandar Lampung.